Factors associated with comorbidity for depression, anxiety, and stress screening in a sample of a Brazilian university’s community during Covid-19 pandemic - Baptista, Cremildo João (2022)
Backgrouund: Mental health is a major public health challenge wordwide and affected people may present more than one mental outcomes simultaneosly. Purpose: To describe the prevalence of comorbidity in screening for depression, anxiety, and stress, as well as determinants of these comorbidity in a university’s community in Mid-West Brazil during the Covid-19. Methods: A cross-sectional descriptive/exploratory study used self-report DASS-21 to screen for mental health. Data from a non-probabilistic sample was obtained online between April 10 and May 25, 2020. Multinomial model was used to identify factors associated with comorbidity. Results: The majority of the sample was students (78.84%), women (65.53%), white (54.18%), single (71.33%), aged 18-29 years old (67.26%), with an overall mean age of 28.3 years (sd = 10.1), 85.63% refered household internet access. 14.48%, 12.42%, and 31.12% screened positive for one, two and all the 3 outcomes, respectively. Students, having children, substance use, presenting Covid-19’s symptoms, worsened self-rated emotional state, and previous mental disorders were associated with comorbidity for depression, anxiety, and stress. Conclusions: Individuals from the studied university’s community experienced psychological disorders, as measured by levels of anxiety, depression, and stress and comorbidity for these outcomes, probably as Covid-19’s initial psychological impact.